Dislocation and node states in bilayer graphene systems - Weckbecker, Dominik; Gupta, Reena; Rost, Fabian; Sharma, S.; Shallcross, Sam (Physical Review B, 2019)
We investigate the electronic structure of realistic partial dislocation networks in bilayer graphene that feature annihilating, wandering, and intersecting partial lines. We find charge accumulation states at partials that are sensitive to Fermi energy and partial Burgers vector but not to the screw versus edge character of the partial. These states are shown to be current carrying, with the current density executing a spiral motion along the dislocation line with a strong interlayer component to the current. Close to the Dirac point, localization on partials switches to localization on intersections of partials, with a corresponding complex current flow around the nodes.
CRIS-Team WoS Importer:2021-10-18